Effect of temperature on the phenology of Chilo partellus (Swinhoe) (Lepidoptera, Crambidae); simulation and visualization of the potential future distribution of C. partellus in Africa under warmer temperatures through the development of life-table parameters - Khadioli, N.; Tonnang, Henri E.Z.; Muchugu, E.; Ong'amo, G.; Achia, Thomas; Kipchirchir, I.; Kroschel, Jürgen; Le Ru, B. (Cambridge University Press, 2014)
Maize (Zea mays) is a major staple food in Africa. However, maize production is severely reduced by damage caused by feeding lepidopteran pests. In East and Southern Africa,Chilo partellusis one of the most damaging cereal stem borers mainly found in the warmer lowland areas. In this study, it was hypothesized that the future distribution and abundance ofC. partellusmay be affected greatly by the current global warming. The temperature-dependent population growth potential ofC. partelluswas studied on artificial diet under laboratory conditions at six constant temperatures (15, 18, 20, 25, 28, 30, 32 and 35 °C), relative humidity of 75±5% and a photoperiod of L12:L12 h. Several non-linear models were fitted to the data to model development time, mortality and reproduction of the insect species. Cohort updating algorithm and rate summation approach were stochastically used for simulating age and stage structure populations and generate life-table parameters. For spatial analysis of the pest risk, three generic risk indices (index of establishment, generation number and activity index) were visualized in the geographical information system component of the advanced Insect Life Cycle modeling (ILCYM) software. To predict the future distribution ofC. partelluswe used the climate change scenario A1B obtained from WorldClim and CCAFS databases. The maps were compared with available data on the current distribution ofC. partellusin Kenya. The results show that the development times of the different stages decreased with increasing temperatures ranging from 18 to 35 °C; at the extreme temperatures, 15 and 38 °C, no egg could hatch and no larvae completed development. The study concludes thatC. partellusmay potentially expands its range into higher altitude areas, highland tropics and moist transitional regions, with the highest maize potential where the species has not been recorded yet. This has serious implication in terms of food security since these areas produce approximately 80% of the total maize in East Africa.